Development of an Unmanned Aerial System for Maritime Environmental Observation - Sunghun Jung; Wonkook Kim (IEEE Access, 2021)
We developed an octocopter-based unmanned aerial system (UAS) to monitor remote environments. The system contains various environmental monitoring sensors for measuring wind speed/direction, temperature, relative humidity, atmospheric pressure, fine dust, and multispectral and RGB data. The UAS consists of an unmanned aerial vehicle (UAV), a ground control station, and a server. We studied its electrical, mechanical, and software (SW) configurations. Specifically, we developed hardware (HW) and SW to control the yaw and gimbal pitch directions of the UAV conveying multispectral and RGB cameras. To prevent the obtained solar reflectance from affecting the multispectral and RGB data and to improve the quality of the obtained data, we maneuvered the yaw so that it would always deviate 135° from the solar azimuth angle, with the sun at its rear. Managing the yaw direction involves controlling the UAV based on a micro air vehicle link message-based robot operating system (ROS). To safely test the UAS performance before the maiden flight in an ocean area, we first evaluated PX4 and ROS-based SW through indoor software-in-the-loop simulation (SILS) via the Gazebo tool. Subsequently, we used an F450 UAV and an actual maritime UAV to sequentially perform pre-flight and flight experiments. This paper explains the system operation scenario, UAS component, and simulation and experimental results. The results reveal that the average yaw angle error during the mission, $\bar {\left |{ θ _{y,des}-θ _{y} }\right |}$ , is approximately 8°, and the average pitch angle of the gimbal during the mission, $\left |{ 50^{° }-\left |{ \bar {θ _{c}} }\right | }\right |$ , is less than 5°.